LncRNA NR-104098 Inhibits AML Proliferation and Induces Differentiation Through Repressing EZH2 Transcription by Interacting With E2F1 - Feng, Yubin; Hu, Shuang; Li, Lanlan; Zhang, Shengpeng; Liu, Jikang; Xu, Xiaoling; Zhang, Meiju; Du, Tianxi; Du, Yan; Peng, Xiaoqing; Chen, Feihu (Frontiers in Cell and Developmental Biology, 2020)
Abundant evidence has illustrated that long non-coding RNA (lncRNA) plays a vital role in the regulation of tumor development and progression. Most lncRNA have been proven to have biological and clinical significance in acute myeloid leukemia (AML), but further studies remain to be needed. In this study, we investigated lncRNA NR-104098 in AML and its specific mechanism. The microarray analysis was performed on NB4 cells. Based on the related analysis results, we identified that lncRNA NR-104098 is a suppressor gene that is significantly upregulated in AML cells. lncRNA NR-104098 could inhibit proliferation and induce differentiation in AML cells in vitro, and also play main role in the mouse xenografts. Mechanically, it was confirmed that lncRNA NR-104098 may effectively inhibit EZH2 transcription by directly binding E2F1 and recruiting E2F1 to EZH2 promoter. In addition, ATPR can significantly increase the expression of lncRNA NR-104098, whereas knocking down NR104098 can inhibit the inhibitory effect of ATPR on the proliferation and induction differentiation of AML cells. Taken together, these results lead to a deeper insight into the mechanism of ATPR induces AML differentiation and inhibits proliferation by inhibiting EZH2 on transcriptional level.